1981
DOI: 10.1083/jcb.88.3.473
|View full text |Cite
|
Sign up to set email alerts
|

Role of collagenous matrices in the adhesion and growth of cells.

Abstract: It has long been appreciated that, for many types of cells, attachment to a substrate is required for their replication. Collagen substrates enhance the growth (64,70,109,238) as well as the differentiation (40,69,85,86,146,161,184), of many cells in culture above that observed with other substrates such as plastic and glass. As discussed in this report, many cultured cells including fibroblasts, myoblasts, hepatocytes, chondrocytes, and certain epithelial cells are thought not to bind directly to the collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
439
2
3

Year Published

1983
1983
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,291 publications
(454 citation statements)
references
References 223 publications
(333 reference statements)
10
439
2
3
Order By: Relevance
“…We have shown (1) that fibronectin is located in the basement membrane region of the lactating rat mammary gland but not in the virgin gland. Fibronectin is involved in cell adhesion (26), and its presence and topographical distribution in the lactating mammary gland may be a consequence of the need to anchor the epithelial cells which are only temporarily exposed to the basement membrane. Similarly, it has been suggested that Thy-1 could be involved in cell-cell and cell-matrix recognition processes in lymphocyte migration.…”
Section: Methodsmentioning
confidence: 99%
“…We have shown (1) that fibronectin is located in the basement membrane region of the lactating rat mammary gland but not in the virgin gland. Fibronectin is involved in cell adhesion (26), and its presence and topographical distribution in the lactating mammary gland may be a consequence of the need to anchor the epithelial cells which are only temporarily exposed to the basement membrane. Similarly, it has been suggested that Thy-1 could be involved in cell-cell and cell-matrix recognition processes in lymphocyte migration.…”
Section: Methodsmentioning
confidence: 99%
“…Collagen, being the main organic component of the ECM, induces positive effects concerning cellular adhesion, proliferation, and differentiation of many cell types in culture (175)(176)(177). Furthermore, collagen exhibits high in vivo biodegradability and excellent biocompatibility (178).…”
Section: Collagen-cap Composite Coatingsmentioning
confidence: 99%
“…The ECM, composed of stromal elements, is synthesized by mesenchymal and epithelial cells through a process which requires dynamic cell-cell interaction (Martin et al 1984). The major components of ECM are collagen, elastin, proteoglycans, glycoprotein fibrils and anchorage proteins such as fibronectin and laminin and its composition varies in different tissues (Kleinman et al 1981). Murray et al (1979) also reported a four-to fivefold increase in the attachment of epidermal cells in collagen IV-coated flasks than in flasks coated with types I-III collagen.…”
Section: Discussionmentioning
confidence: 99%